Information Motivation Behavior Determinants of Decision to Quit Smoking - Danu Aprilianto; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Cigarette sales in Indonesia continue to increase, as does the number of people who consume cigarettes, children who smoke, and also deaths caused by smoking. This study aimed to analyze the factors that influence the decision to stop smoking in the Special Region of Yogyakarta using the information motivation behavior skills theory. Subjects and Method: This research is an analytical observational study with a cross-sectional study approach conducted in the Special Region of Yogyakarta in June-July 2023. There were 212 adults consisting of 153 active smokers and 59 former smokers. The dependent variable is the decision to stop smoking. The independent variable is Information Motivation Behavior Skill (IMB). Data was collected using a questionnaire distributed online and analyzed using a path analysis test. Results: Good information (b= 1.25; 95% CI= 0.32 to 2.17; p< 0.008) and high motivation (b= 2.23; 95% CI= 1.54 to 2.9; p< 0.001) were associated with smoking cessation skills, smoking cessation skills good (b= 1.72; 95% CI= 1.01 to 2.43; p< 0.000) is associated with the decision to stop smoking. Conclusion: Good information, high motivation, and smoking cessation skills are statistically related directly and indirectly to the decision to stop smoking.